Lisbon as a literary tourism site: Εssays of a digital map of Pessoa as a new trigger - Anjo, Ana Margarida (2021)
Purpose: The purpose of this paper is to analyse the potential of literary tourism in Portugal and explore the advantages of creating a digital literary map about the places associated with the widely renowned Portuguese author Fernando Pessoa (hereafter Pessoa), as well as the places that he suggests in one of his works, a tourist guide of Lisbon: What the Tourist Should See (1925). Methods: Firstly, a study of the state of art of the key concepts was made in order to apply them in the second part, the methodology, in the case of studying Lisbon from Pessoa's perspective. Then, allying personal taste for the writer/author with interest in cultural promotion gave rise to a digital literary map of Pessoa’s Lisbon. Methodologically, a questionnaire was applied covering a sample of 173 valid literary tourists. Results: literary tourism should be an object of in-depth studies, as it tends to be beneficial for cultural promotion of tourist destinations and products, specifically for literary tourists. Further limitations, implications and future suggestions of this study are provided. Implications: This paper is the first to empirically test literary tourism, proposing a digital literary tourism map. Regarding the main findings, there is high interest